FRI0185 Factors determining work instability in patients with axial spondyloarthritis. (12th June 2018) - Buche, A.S.; Preston, L.; Barkham, N.
Abstract : Background: Work instability is defined as mismatch between the employee's ability to work and the employer's expectations 1 . 50% of Ankylosing spondylitis patient lose their job due to disease activity and 50% of those in job face work instability and job retention problem 2 . Work disability is preceded by a period of work instability, which can be measured by the Ankylosing spondylitis work instability scale (ASWIS) 1 . Objectives: To determine the factors responsible for work instability in patients with Axial spondyloarthritis (axSpA). Methods: Patients attending the Spondyloarthritis clinic at a UK centre from 2013 to 2017, were included, if in employment, and diagnosed with axSpA according to ASAS criteria. Number of patients having low(WIS ≤10) and moderate to high (WIS 11–20) and corresponding parameters were noted. Numerical values were analysed using Spearman rank test and categorical values using Pearson's test. Multiple regression analysis was done. P value≤0.05 was considered significant. Results: Of total 255 patients, 139 were in employment (54.5%).97 were male and 42 were female. Mean age was 43.5 years (20–78 years). 59 patients in manual and 80 patients in non-manual job type, 52 had non-radiographic axSpA (nrSpA) and 87 had radiographic axSpA (rSpA). Mean diagnostic delay was 8 years (0–37 years). Mean ASWIS score was 10.43 (0–20). 75 patients (53.9%) were in Low WIS category and 64 (46%) in moderate to high WIS category. BASDAI and BASFI are found to be significantly correlating with WIS for the whole cohort. Conclusions: Work instability is prevalent in axSpA, in all job types. Main factors contributing to work instability are disease activity (BASDAI) and function (BASFI). Drivers for work instability may be different in radiographic and non-radiographic patients. A prospective study will evaluate the impact of use of biologic on work instability. References: [1] Gilworth G, Emery P, Barkham N, Tennant A, et al: Reducing work disability in Ankylosing spondylitis-development of a work instability scale for AS. BMC Musculoskeletal Disord2009;10:68. [2] Barkham N, Kong KO, Tennant A, Emery P, et al. The unmet need for anti-tumour necrosis therapy in ankylosing spondylitis. Rheumatology2005;44:1277–1281. Acknowledgements: UCB contributed funding for part of this research, but had no input in collection, analysis of data or preparation of abstract. Disclosure of Interest: None declared